P05.50 Hypofractionated stereotactic radiation therapy (HSRT) in skull base meningiomas. (19th September 2018) - Franzese, C; Navarria, P; Clerici, E; Comito, T; Pessina, F; Bello, L; Reggiori, G; Tomatis, S; Scorsetti, M
Abstract: Background: Skull base meningiomas, represent a subgroup of tumors in which a complete surgical removal is rarely achieved. Stereotactic radiotherapy, either as hypofractionated stereotactic radiotherapy (HSRT) or single dose radiosurgery, has emerged as a valuable first option in selected patients, or after incomplete surgical resection. Radiosurgery is used for small lesions away from critical structures. Limitations are represented from large meningioma, close to critical structures for the high risk of late toxicity and radionecrosis. To date few date are published about HSRT. Patients with large skull base meningioma has been treated with HSRT in our Institution. The aim of this evaluation has been to assess the impact of HSRT in term of local toxicity, patients symptoms relief and local control rate. Material and Methods: This prospective observational study includes patients with MRI diagnosis of skull base meningioma. Patients underwent HSRT in case of one or more of the following: (1) large skull base meningioma, (2) proximity of critical structures, (3) growing residual tumor after surgery, (4) symptomatic patients (with stable and impairing symptoms since more than 3 months and requiring medications for their control), (5) contraindication to surgical resection. All patients were treated with a total dose of 30 Gy in 5 fractions. Treatments were optimized for Volumetric Modulated Arc therapy. Relief from symptoms, local control (LC), overall survival (OS) and toxicity rates were analyzed. Results: Fifty-five patients were included in the study and treated with a dose of 30 Gy in 5 fractions with volumetric modulated arc therapy (RapidArc). Thirty-six patients were symptomatic before treatment. Tumors were located in anterior skull base in 8/55 cases, in middle skull base in 25/55 and in posterior skull base in 22/55. HSRT was performed as first treatment in 36 (65%) patients, in 19 (35%) patients it followed a previous partial resection. Median follow up was 48 months. Clinical remission of symptoms, complete or partial, was obtained in the vast majority of patients after treatment. Out of the 36 symptomatic patients, partial remission occurred in 18 (50%) patients and complete remission in 18 (50%). All asymptomatic patients retained their status after treatment. No severe neurologic toxicity grade III-IV was recorded. No increase of meningioma in the same site of treatment occurred; 32 (62%) patients had stable disease and 18 (38%) patients had tumor reduction. The mean tumor volume after treatment was 10.8 ± 17.8 cm3 compared with 13.0 ± 19.1 cm3 before treatment (p = 0.02). The mean actuarial OS was 72 months. The 1- and 2-years OS was 92.9%. Conclusion: In our experience, HSRT with VMAT given at ablative doses has proven to be feasible with limited morbidity. Local control and durability of results suggest for a routine application of this approach in properly selected cases.